A study of the effect of irradiation and heat treatment on structural properties and transitions Electronegativity of indium-doped and undoped CuO films (Journal of the College of Basic Education, 2023)
And by studying the X-ray diffraction pattern, the nature of crystallization of the films was diagnosed.Where the tests showed that the pure and doped copper oxide films have a crystal structureMultiplayer.The research included studying the absorbance and transmittance spectrum of the prepared films, and calculating theAbsorption coefficient and the forbidden energy gap for the allowed direct and indirect transitions.The results showed that the doping led to an increase in the absorption coefficient and a decrease in the value ofThe energy gap is due to the allowed direct transitions.The effect of irradiation on the structural properties and electronic transitions of membranes was studied.CuO:In , CuO . The results of the structural properties study showed that the irradiation led toA decrease in the intensity of the peaks and a decrease in their sharpness, meaning that the membrane material has become less crystallized due toThe effect of radiation. When studying electronic transitions, irradiation led to an increase in the value ofThe forbidden energy gap.